HIKAYAT RAJA-RAJA PASAI: ANALISIS AKTANSIAL GREIMAS TERHADAP STRUKTUR LEGITIMASI DINASTI - Wahyuni, Indah (Tambo: Journal of Manuscript and Oral Tradition, 2025)
This study analyses the construction of power legitimacy in the Hikayat Raja-raja Pasai (HRRP) by utilising A. J. Greimas actantial model synthesis and Pierre Bourdieu’s symbolic power theory. Using qualitative text analysis methods, this study focuses on mapping actant functions and explaining how narrative structures function as a mechanism for neutralising authority. The findings show that the legitimacy of the Pasai kings was constructed multidimensionally through a recurring narrative pattern (qualification, action, and recognition), which transformed the subjects from potential leaders into legitimate ones. This process was reinforced by the sacralisation of power through supernatural signs and the accumulation of symbolic capital, so that the dynasty’s authority appeared to be a natural and indisputable destiny. The conclusion of this study confirms that the HRRP functions as an ideological text that actively produces and legitimises power by closely linking it to Islamic identity and the socio-cultural values of early Malay society.